Pengaruh Waktu Tinggal dan Media Tanam pada Constructed Wetland untuk Mengolah Air Limbah Industri Tahu - Muhammad Al Kholif; Pungut; Sugito; Joko Sutrisno; Winda Sulistyo Dewi (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
Tofu industry waste pollution is still a serious problem. The high burden of tofu industrial waste pollutants is still a major problem. besides, the unavailability of the budget for processing and the limitations of a cheap and efficient treatment system are factors supporting the pollution of tofu waste in the environment. This study examines the efficiency of reducing BOD5 and COD treated with constructed wetlands using water jasmine plants (Enchinodorus palaefolius). The system used is the wetland subsurface with continuous flow. The media used include sand and biochar with a residence time of 12 hours 18 hours. Whereas pH, temperature, and flow rate are conditioned as control variables. The greatest efficiency of BOD5 and COD occurs in reactors using biochar media and a residence time of 18 hours with an efficiency of BOD5 of 50.52% and COD of 55.02%.